The Budgetary Framework for Research and Innovation in Cameroon: An Analysis of a Missed Opportunity in Public Higher Education - KANA ETOUNDI René Rodrigue Lionel; NDJEBAKAL SOUCK Emmanuel; BOUBA Bachir (Contemporary Research Analysis Journal, 2026)
In 2007, Cameroon adopted a program-based public finance system grounded in Results-Based Management (RBM). In higher education, this policy is implemented through four programs, including the program dedicated to the development of university research and innovation. The Ministry of Higher Education and Scientific Research’s (MINESUP) Strategic Performance Framework (CSP 2022–2030) structure this program into objectives, indicators, and actions. Its budget logic framework also identifies the actors and those responsible for the program’s activities. This article analyzes how this budget framework reveals a failure of participatory governance in university research and innovation (R&I). The study is based on an exclusively qualitative, documentary approach. It involves a critical analysis of the budget logic framework cross-referenced with other official sources. The analysis is conducted through the lens of a theoretical approach focusing on the inadequate implementation of NMP standards and tools. The results highlight three major symptoms of this failure : (1) a top-down structure that excludes scientific stakeholders from budgetary decisions; (2) the failure to incorporate scientific priorities; (3) a focus on administrative rather than scientific indicators. In conclusion, the article demonstrates that this budgetary logical framework functions as a tool for bureaucratic recentralization under the guise of managerial modernity. It advocates for a participatory revision of this system to finally align program-based budgetary governance with the actual needs of research.